Biological sciences notable research and discoveries - Kirkland, Kyle. (New York, NY Facts on File, 2010)
Investigates the research and discoveries made by scientists who expanded the frontiers of physiology, genetics, ecology, botany, and molecular biology.
Brain imaging: searching for sites of perception and consciousness -- The human genome in health and disease -- Protein structure and function -- Biodiversity: the complexity of life -- The biology and evolution of viruses -- Regeneration: healing by regrowing -- Final thoughts.
Includes bibliographical references and index.
Keywords: Medical sciences; Biology; Discoveries in science